Faking of personality tests in different motivational contexts - Galić, Zvonimir (Array, 2006)
A major concern in using personality tests for personnel selection has been their potential for response distortion in social desirable direction. Faking personality test in order to create a favorable self-presentation is certainly possible, but there are equivocal findings to what extent is it present in selection setting and what social desirable responding represents. Most of the studies showing existence of response distortion compared job-applicants to an independent sample and treated social desirable responding as unitary construct with contaminating effect. Our study had two aims: first was to use a dependent sample to test the differences on personality dimensions between selection and honest setting. Second aim was to test Paulhus’ model, which states that social desirability has two distinct components: self-deception and impression management. We compared the two components between different motivational contexts. The research was done on applicants for military pilots (N=231). They completed our inventory as part of a regular selection battery and, a few months later, under anonymity. Results showed differences on personality and social desirability scales: in selection situation applicants described themselves as more conscientious and agreeable and showed more impression management. Theoretical and practical implications of results will be discussed.